Resveratrol inhibits skin squamous cell carcinoma proliferation, migration and invasion through up-regulating miR-126 - Zhang, Bo; Lari Najafi, Moslem (Cellular and Molecular Biology, 2020)
The current experiment was performed to explore the effect and possible mechanism of resveratrol on the proliferation, migration and invasion of skin squamous cell carcinoma cells (HSC-5). Tetramethyl azozo blue (MTT) method, Transwell experiment and real-time fluorescence quantitative PCR (RT-qPCR) were used to detect the effects of resveratrol intervention on the proliferation, migration and invasion of HSC-5 cells and the expression of miR-126. The miR-126 mimics and inhibitors were transfected into HSC-5 cells, and the effects of up-regulation or down-regulation of HSC-5 expression on the proliferation, migration and invasion of HSC-5 cells were detected. The miR-126 inhibitor was transfected into HSC-5 cells, and the effects of resveratrol intervention on HSC-5 cell proliferation, migration and invasion, and Î²-catenin protein expression were detected. After resveratrol intervention, the growth rate, migration and invasion of HSC-5 cells were significantly reduced, miR-126 expression was significantly increased, and Î²-catenin protein expression was significantly reduced (p<0.05). After up-regulating the expression of miR-126, the growth rate, migration and invasion of HSC-5 cells were significantly reduced (p<0.05). After down-regulating the expression of miR-126, the growth rate, migration and invasion of HSC-5 cells were significantly increased (p<0.05). Down-regulation of miR-126 expression could reverse the effects of resveratrol intervention on HSC-5 cell proliferation, migration and invasion, and Î²-catenin protein expression (p<0.05). Resveratrol could inhibit the proliferation, migration and invasion of skin squamous cell carcinoma cells, which may be related to the up-regulation of miR-126 to inhibit the Wnt / Î²-catenin signaling pathway.